2020
DOI: 10.1111/are.14591
|View full text |Cite
|
Sign up to set email alerts
|

Sesbania aculeata leaf meal as replacer of de‐oiled rice bran in aquaculture feed: Growth, IGF‐1 expression, metabolic and biochemical responses in Cyprinus carpio ( Linnaeus 1758 )

Abstract: Feed represents the single largest input in commercial aquaculture comprising about 60% of the total operating cost (De Silva & Anderson, 1995). The present requirement of aquafeed is estimated to be 60 million tonnes (FAO, 2014). Presently, both protein and energy rich conventional dietary ingredients are of short supply which necessitates incorporating unexplored unconventional locally available ingredients in aquafeed. Oil cakes are conventional protein sources used for carp culture in Asia along with deoil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 56 publications
5
17
1
Order By: Relevance
“…Comparatively, lower WG % was observed in the control group, which was not significantly ( p > 0.05) different from the T20 group. The highest FCR values were observed in the control and T20 group, which complements the growth data (Anand et al, 2020; Maiti et al., 2019). The protein efficiency ratio was also higher in treatment groups compared to the control group.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Comparatively, lower WG % was observed in the control group, which was not significantly ( p > 0.05) different from the T20 group. The highest FCR values were observed in the control and T20 group, which complements the growth data (Anand et al, 2020; Maiti et al., 2019). The protein efficiency ratio was also higher in treatment groups compared to the control group.…”
Section: Discussionsupporting
confidence: 86%
“…The findings of Kumar et al (2017), Kumar Sahu, and Ranjan (2018), Kumar, Sahu, Shamna, et al (2018), Lovell (1989)), Meshram et al. (2018), Ranjan, Sahu, Deo, Kumar, Kumar, et al (2018), Ranjan et al (2018) and Anand et al (2020) also reported the similar findings. GSI and HSI showed no significant difference ( p > 0.05) between different experimental groups.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations